Regulation of Minimum Notary Fees for the Preparation of Deeds in Indonesia and South Korean as an Effort to Enforce Notary Professionalism - Innayah Ananda Cahyani; Yudho Taruno Muryanto; Jadmiko Anom Husodo (Siber International Journal of Advanced Law (SIJAL), 2026)
This study analyzes the minimum notary fee regulations in the preparation of deeds in order to uphold the professionalism of the notary profession through a comparative study of notary law in South Korea. The purpose of this study is to analyze the minimum notary fee regulations, which often lead to unhealthy competition among notaries in Indonesia. This study uses a normative research method with a legal and comparative approach. The results of this study show that the establishment of notary fees in Indonesia is an urgent need from the perspective of legal certainty and justice. The result is legal uncertainty for the public who use notary services and a decline in the dignity of notaries due to price cutting. In South Korea, because fees are public and transparent and maintain the professionalism of notaries, the ideal honorarium in Indonesia that can provide justice is: clear legal regulations, minimum fee regulations.